HUBUNGAN STRUKTUR KEPEMILIKAN, TINGKAT UTANG, DIVIDEN, DAN NILAI PERUSAHAAN DALAM MENGURANGI KONFLIK KEAGENAN DI INDONESIA - Sri Dwi Ari Ambarwati; Khoirul Hikmah (University of Merdeka Malang, 2014)
This research tried to analyze substitution relationship among debt policy, dividend and insider ownership structure as the agency control mechanism on manufacturing firms in period 2005-2009. The hypothesis proposed in this paper were there was a substitution relationship between insider's ownership and debt policy in reducing agency conflict, there was a substitution relationship between debt and dividend policy in reducing agency conflict and there was substitution relationship between insider's ownership and dividend policy in reducing agency conflict. This research used purposive sampling method to determine samples and there were 42 firms as the samples. The analysis instrument used was simultaneous equation model by using two stages least square method. These empirical results verified that debt and dividend policy was determined by simultaneous, while insider ownership did not influence debt policy. Hypothesis test showed that there was no substitution relationship between insider's ownership and debt policy in reducing agency conflict, there was substitution relationship between debt and dividend policy in reducing agency conflict and there was substitution relationship between insider's ownership and dividend policy in reducing agency conflict. Because as a whole, eventhough not fully, there was simultaneity among debt policy, insider's ownership and dividend it was expected to increase firm value.